Musical Images from Sufferers: “Entangled” – Genesis - Franca Daniele (European Scientific Journal, ESJ, 2020)
The present paper carries out a textual, discourse and semantic analysis of the song Entangled, a masterpiece by the English band Genesis. The song describes a patient living in a dream-like state, having many similarities and parallels with the state of being affected by Covid-19 in the final stages of the disease. The most overt message deriving from analyzing the words and the discourse in Entangled is the prevailing-type pattern that evidences the strong imbalance existing in a relationship between a doctor and a patient. The inaffable music and voices join in a coral-like song that seems to have links with serenades, charms, prayers, and with unknown dimensions. The enchanting images produced by Entangled evoke a calm, dream-like state where the listener is carried inside the soft ripples of the rhymes and verses that combine and overlap perfectly with the flowing rhythm and the purely magical music.